HABITUASI TAWADHU DALAM PENDIDIKAN AKHLAK SANTRI DI PONDOK PESANTREN MULTIDIMENSI AL-FAKHRIYAH MAKASSAR - Ahmad Julfikar (ISTIQRA: Jurnal Hasil Penelitian, 2024)
The purpose of this study was to analyze the concept of habituation of humility in the process of moral education of students implemented by the Multidimensional Islamic Boarding School of AL-Fakhriyah Makassar. The focus of this study includes. Strategy of habituation of humility in moral education of students and Implications of habituation of humility in the moral education of students. This research is qualitative descriptive, data sources come from the supervisor of the Islamic boarding school, head of campus, head of Islamic boarding school, and students. Data were collected through observation, interviews, and documentation then analyzed. The results of the study show that moral education in habituating humility is used through Role models, the Habituation of reading books and discipline of worship, Mauidzah Hashanah, Guidance, and counseling. The implications of the habituation of humility can be seen through communication patterns, interaction patterns, and daily activities of students. 1) politeness when speaking, 2) Tabe when passing in front of the teacher, 3) shaking hands when meeting, and 4) being humble by respecting and honoring each other. To enrich this research, the recommendation that needs to be added is that an integrative approach in moral education needs to be strengthened by including the values ​​of humility in all aspects of the lives of students. In addition, Islamic boarding school supervisors and other administrators need to be given regular training on moral habituation techniques, effective communication, and character building so that they can provide an example that can be imitated by students.